Determinação dos sorovares de haemophilus parasuis relacionados com a doença de glässer no Brasil - Espíndola, Julia Pires (2017)
Glässer's disease (GD) is an emerging bacterial disease of great importance to the world's pig farming. Its etiologic agent is Haemophilus parasuis (H. parasuis), a fastidious, phenotypically heterogeneous Gram negative bacterium that can trigger an important systemic pathology in pigs characterized by fibrinous polyserositis, polyarthritis and meningitis. H.parasuis is classified in 15 serovars (SV), however, a growing number of non-typeable (NT) strains and related to outbreaks of GD have emerged, demonstrating the genetic variability of this microorganism. Brazil stands out as one of the main countries in this production chain, being the fourth largest in swine production and exportation. Studies related to typing clinical strains of H. parasuis that are circulating in Brazil are scarce, even with its importance, and there are no studies that demonstrate the national screening of distribution of the serovars in the main producing regions of swine. In our country, the immunoprevention of the H. parasuis infections relays in commercial vaccines based on monovalent and bivalent bacterinsinactivated with formalin and potentiated with aqueous or oily adjuvants. Due to the problems related to the protective capacity of these vaccines, mainly due to the high phenotypic variability of the different serovars of this pathogen andthe little or absent cross-protection conferred by a single serovar, isolation and characterization of strains involved in a GDoutbreak are determinant for the development of more racional vaccine-based preventive program. In response to the national scenario related to H. parasuis and GD, we present here the H. parasuis serovars involved in outbreaks of DG in Brazil, their geographic distribution, the temporal effect on the prevalence of serovars, and the impact of these work in the vaccines actually used. To reach these objectives, 460 clinical isolates of H. parasuis from ten Brazilian states, covering the main swine producing regions, were analyzed. The strains were typed by multiplex PCR technique developed by Howell et al. (2015), and the differentiation of serovars 5 and 12 was performed using the modified indirect hemagglutination technique developed by Lorenson et al. (2017). Our results show that the most prevalent serovars are SV 4 (26.6%), NT (17.6%), SV 1 (13.1%), SV 14 (12.6%) and SV 5 (10.7%). Taking into account the virulence of serovars, according to the classification proposed by Kielstein and Rapp-Gabrielson (1992), more than half of all isolates belong to the highly virulent serovars group (51.0%) and 31.4% to the serovars moderately virulent group. We observed that NTstrains were fundamentally isolated from the respiratory system, involving lungs (64.9%), nasal area (13.0%) and trachea (10.4%). On the other hand, serovars 5 and 14 were basically isolated from brain, heart, joints and cavitary fluids. When related to virulence, 62.5% of the highly virulent serovars were isolated from systemic sites and the others from the respiratory system. Regarding the geographic distribution, we observed the presence of serovars 1, 4, 5, 5/12, 14, 15 and NS in almost all analyzed states. On the other hand, serovars 2 and 13 were only detected in SC, MT and MG, respectively; in addition, serovar 12 was basically restricted to RS. The states with the highest number of analyzed samples were MG and SC, a fact that may be related to the high densities of pigs produced in these regions. In addition, we observed that the number of field isolates and amongst them of highly virulent strains have increased between 2013 to 2016. In summary, we present an update of H. parasuis serovars associated with GD in Brazil, and we highlight that the commercial vaccines available in our country do not include 76.3% of the serovars present on our pig production farms. Thus, the short-term success of GD prevention in our country is conditioned by the use of autogenous vaccines and, in the long term, an update of the antigenic composition of current commercial vaccines.